Service Quality Assessment In Ecotourism Areas: The Case Of Tasik Kenyir Resort Management - Rahman, Faiz Abd (2012)
In a recent debate to improve resorts management in ecotourism area, the suitability of customer satisfaction survey in order to improve the quality of service in the resorts and in the ecotourism has become an issue. The main purpose of the study is to measure the level of customer satisfaction with products and services offered and to identify the factors that influence customer satisfaction.This study was conducted in Kenyir Lake Terengganu. Kenyir Lake was chosen as the study area because these areas meet the characteristics of ecotourism area.